2022
DOI: 10.1038/s41522-022-00285-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel endolysins targeting Gardnerella vaginalis biofilms to treat bacterial vaginosis

Abstract: Bacterial vaginosis (BV) is a recurrent dysbiosis that is frequently associated with preterm birth, increased risk for acquisition of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). The overgrowth of a key pathobiont, Gardnerella vaginalis, as a recalcitrant biofilm is central to the development of this dysbiosis. Overgrowth of vaginal biofilms, seeded by initial G. vaginalis colonization, leads to recurrent symptomatic BV which is poorly resolved by classically used antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…Recombinant endolysins candidates were produced as previously reported [ 12 ]. In short, pCCB7.1, a pET30a(+) vector harbouring the codon optimised ccb 7.1 gene sequence, was transformed into E. coli BL21(DE3).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant endolysins candidates were produced as previously reported [ 12 ]. In short, pCCB7.1, a pET30a(+) vector harbouring the codon optimised ccb 7.1 gene sequence, was transformed into E. coli BL21(DE3).…”
Section: Methodsmentioning
confidence: 99%
“…Given this mechanism of action, these enzymes have good promise as therapeutics to be harnessed by clinicians. Previous studies have shown these enzymes are capable of lysing Gram-positive bacteria which lack an outer lipopolysaccharide membrane when added exogenously to culture media and more complex models of disease [ [12] , [13] , [14] ]. Interestingly, endolysins have also shown promise as antimicrobial agents against Gram-negative bacteria [ 15 ], despite their diderm cell wall structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these approaches is based on the use of phage components such as endolysins. In a study by Arroyo-Moreno et al 9 the authors show that endolysins can disrupt Gardnerella vaginalis both in single species and polymicrobial biofilms with no effect on microorganisms from the commensal vaginal flora nor the emergence of resistance, offering a promising strategy to combat bacterial vaginosis. An alternative approach to identify novel antimicrobials is to search from them in microbiomes as they are a great resource for bioactive molecules which has been very much unexploited.…”
mentioning
confidence: 99%